A global perspective on FOXO1 in lipid metabolism and lipid-related diseases. (April 2017) - Li, Yue; Ma, Zhiqiang; Jiang, Shuai; Hu, Wei; Li, Tian; Di, Shouyin; Wang, Dongjin; Yang, Yang
Abstract: Lipid metabolism is a complex physiological process that is involved in nutrient adjustment, hormone regulation, and homeostasis. An unhealthy lifestyle and chronic nutrient overload can cause lipid metabolism disorders, which may lead to serious lipid-related diseases, including obesity, non-alcoholic fatty liver disease (NAFLD), and type 2 diabetes mellitus (T2DM). Therefore, tools for preventing dysfunctional lipid metabolism are urgently needed. The transcription factor forkhead box protein O1 (FOXO1) is involved in lipid metabolism and plays a critical role in the development of lipid-related diseases. In this review, we provide a global perspective on the role of FOXO1 in lipid metabolism and lipid-related diseases. The information included here may be useful for the design of future studies and advancing investigations of FOXO1 as a therapeutic target.